Moisture Sensitive Smart Yarns and Textiles from Self‐Balanced Silk Fiber Muscles. (7th March 2019) - Jia, Tianjiao; Wang, Yang; Dou, Yuanyuan; Li, Yaowang; Jung de Andrade, Monica; Wang, Run; Fang, Shaoli; Li, Jingjing; Yu, Zhou; Qiao, Rui; Liu, Zhuangjian; Cheng, Yuan; et al.
Abstract: Smart textiles that sense, interact, and adapt to environmental stimuli have provided exciting new opportunities for a variety of applications. However, current advances have largely remained at the research stage due to the high cost, complexity of manufacturing, and uncomfortableness of environment‐sensitive materials. In contrast, natural textile materials are more attractive for smart textiles due to their merits in terms of low cost and comfortability. Here, water fog and humidity‐driven torsional and tensile actuation of thermally set twisted, coiled, plied silk fibers, and weave textiles from these silk fibers are reported. When exposed to water fog, the torsional silk fiber provides a fully reversible torsional stroke of 547° mm −1 . Coiled‐and‐thermoset silk yarns provide a 70% contraction when the relative humidity is changed from 20% to 80%. Such an excellent actuation behavior originates from water absorption‐induced loss of hydrogen bonds within the silk proteins and the associated structural transformation, which are corroborated by atomistic and macroscopic characterization of silk and molecular dynamics simulations. With its large abundance, cost‐effectiveness, and comfortability for wearing, the silk muscles will open up additional possibilities in industrial applications, such as smart textiles and soft robotics. Abstract : Moisture‐sensitive silk muscles are made based on volume expansion, which originates from water absorption‐induced loss of hydrogen bonds within the silk proteins and the associated secondary structural transformation. Owing to its large abundance, cost‐effectiveness, and comfortability for wearing, the silk muscles will open up additional possibilities in industrial applications, such as smart textiles.